2021
DOI: 10.1111/ijn.13034
|View full text |Cite
|
Sign up to set email alerts
|

When health care workers became patients with COVID‐19: A qualitative study

Abstract: Aims This study aimed to describe the experiences of nurses and other health care workers who were infected with coronavirus disease 2019. Methods An empirical phenomenological approach was used. Sixteen participants were recruited in Wuhan using purposive and snowball sampling. Semistructured, in‐depth interviews were conducted by telephone in February 2020. Interviews were transcribed verbatim and analysed following Colaizzi's method. Results Two themes emerged: (1) Intense emotional distress since becoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The current findings were consistent with previous studies where the exposed HCWs reported increased levels of anxiety, depression and hostility (Chou et al, 2020;Maunder et al, 2006;Park & Park, 2020). Consistent with the qualitative findings among infected HCWs, the psychological distress mostly came from uncertainty towards the results of exposure (Du et al, 2022).…”
Section: Personal Awareness and Alertnesssupporting
confidence: 92%
See 1 more Smart Citation
“…The current findings were consistent with previous studies where the exposed HCWs reported increased levels of anxiety, depression and hostility (Chou et al, 2020;Maunder et al, 2006;Park & Park, 2020). Consistent with the qualitative findings among infected HCWs, the psychological distress mostly came from uncertainty towards the results of exposure (Du et al, 2022).…”
Section: Personal Awareness and Alertnesssupporting
confidence: 92%
“…The current findings were consistent with previous studies where the exposed HCWs reported increased levels of anxiety, depression and hostility (Chou et al, 2020 ; Liu, Yang, et al, 2020 ; Maunder et al, 2006 ; Park & Park, 2020 ). Consistent with the qualitative findings among infected HCWs, the psychological distress mostly came from uncertainty towards the results of exposure (Du et al, 2022 ). These findings indicated that timely psychological assessment and interventions should be provided to the HCWs immediately after their occupational exposure.…”
Section: Discussionsupporting
confidence: 82%
“…Table 2 summarizes the included studies conducted mainly in China ( K = 6) (Chun et al, 2021; Dou et al, 2021; He et al, 2021; Jiang et al, 2022; Luo et al, 2022; Zhang et al, 2021), Turkey ( K = 4) (Özlük & Bikmaz, 2021; Ruveyde & Bulut, 2022; Savas et al, 2022; Topdemir et al, 2022), Iran ( K = 2) (Safiri et al, 2022; Shali et al, 2022), Italy ( K = 2) (Piredda et al, 2022; Simeone et al, 2022), Zimbabwe ( K = 1) (Moyo et al, 2022), Indonesia ( K = 1) (Siagian & Rantung, 2022), and the United Arab Emirates ( K = 1) (Khaled et al, 2022) between 2021 and 2022. These seventeen studies involved 271 nurses, predominantly female, and covered a wide age range.…”
Section: Resultsmentioning
confidence: 99%
“…These seventeen studies involved 271 nurses, predominantly female, and covered a wide age range. The sample was diverse in terms of work settings, including Emergency ( N = 12) (Dou et al, 2021; Luo et al, 2022; Özlük & Bikmaz, 2021; Zhang et al, 2021), ICU ( N = 9) (Luo et al, 2022; Özlük & Bikmaz, 2021; Simeone et al, 2022), Internal Medicine ( N = 7) (Dou et al, 2021; Luo et al, 2022; Zhang et al, 2021), Surgery ( N = 5) (Dou et al, 2021; Luo et al, 2022; Zhang et al, 2021), and Obstetrics and Gynecology ( N = 3) (Dou et al, 2021; Özlük & Bikmaz, 2021; Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare workers (HCWs), especially those who acquired COVID-19, have reported negative social reactions and various forms of stigmatization during the pandemic. [1] , [2] , [3] , [4] These reactions took several forms including avoidance, isolation and harassment. The aim of this study was to examine the living conditions, social determinants, and experiences during the COVID-19 pandemic among employees who recovered from COVID-19 at a large tertiary referral cancer hospital in India, which was designated as a COVID-19 care centre for cancer patients.…”
Section: Introductionmentioning
confidence: 99%